Analisis Sosiologis Fenomena dan Realitas Pada Masyarakat Siber - Nopti Kurnia Illahi; Rafinita Aditia (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The development of information technology has created a new artificial and virtual space, namely cyberspace. Cybercommunity is a virtual life in a virtual world that is built through a computer network but remains connected, and has its own social life. The phenomena and realities that occur in cyber society are certainly different from ordinary people. So this study will discuss the sociological analysis of phenomena and reality in cyber society. The approach used in this research is a qualitative approach with a descriptive method. This research is not intended to obtain external validity, but rather aims to gain an understanding of reality in its specific context. The results showed that the formation of cyber communities was initially small and was developed using a spider web pattern to form a large community. This cyber society ultimately forms a cyber culture and has its own stratification. However, the presence of cyber society has not only positive but also negative impacts, one of which is cyber crime. For this reason, cyberlaw is needed so that the life of the cyber community can run better.